2005
DOI: 10.1111/j.1526-4610.2005.05162.x
|View full text |Cite
|
Sign up to set email alerts
|

A High Incidence of Migraine With Aura Among Morbidly Obese Women

Abstract: The unusually high incidence of migraine with aura can be attributed to extraovarian production of estrogen and estradiol in the adipose tissue. Further study is indicated to explore the therapeutic role of weight loss in headache care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
51
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 10 publications
14
51
0
2
Order By: Relevance
“…Furthermore this observation was supported by Peres et al so that migraine headache was reported as 66% of obese patients in comparison with 18.5% of non-obese subjects (14). Moreover other studies have suggested that there is the association between migraine and obesity among men and in reproductive age women (39) and also in youngster age (37).…”
Section: The Association Between Morbid Obesity and Migraine Headachesupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore this observation was supported by Peres et al so that migraine headache was reported as 66% of obese patients in comparison with 18.5% of non-obese subjects (14). Moreover other studies have suggested that there is the association between migraine and obesity among men and in reproductive age women (39) and also in youngster age (37).…”
Section: The Association Between Morbid Obesity and Migraine Headachesupporting
confidence: 75%
“…During the recent years, some investigation revealed that there are a considerable proportion of morbidly obese female among candidates for bariatric surgery who suffers from migraine. Horev et al (39) show that incidence of migraine headache among morbid obese individual was 48% higher as compared with non-obese control groups (40). Furthermore this observation was supported by Peres et al so that migraine headache was reported as 66% of obese patients in comparison with 18.5% of non-obese subjects (14).…”
Section: The Association Between Morbid Obesity and Migraine Headachesupporting
confidence: 71%
“…Horev et al [16] reported that the frequency of aura was more frequent in patients with overweight. The main observation of this study is controversial because of the reduced sample size, lack of controls and the selection of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…No specifically study has been conducted on migraine in the Parakou University in the North of Benin. Other studies conducted in various areas estimate the relationship between body mass index and migraine [8] showed contradictory results [9,10].…”
Section: Introductionmentioning
confidence: 99%